Avaliação da qualidade de vida relacionada à saúde de mulheres com câncer de mulheres com câncer de mama e ovário em quimioterapia adjuvante - Leitão, Nilza Maria de Abreu (2012)
This research work aimed to assess the Health-Related Quality of Life of women with breast and gynecological cancer undergoing adjuvant antineoplastic chemotherapy. A descriptive study with cross-sectional design and quantitative approach. The research took place at the chemotherapy ward of a nonprofit tertiary referral hospital for cancer surgery in Fortaleza-CE, Brazil. The study sample consisted of 72 women. Data collection happened from April to May 2012. After given informed consent, all women participated in individual interviews and completed the research protocol consisting of a questionnaire of socio-demographic data and the scale of the European Organization for Research and Treatment of Cancer: Quality of Life Evaluation in cancer patients (QLQ-C30 version 3.0). From the analytical study, we highlight the following results: most patients considered the overall QOL measure as “great” with predominant scores 06 and 07. The sub-scale of the item for Social Functioning had the best score with 54.2. On the other hand, we observed the worst performances of women in the Role Performance, Emotional, Physical, and Cognitive Functioning. Regarding the most frequent or intense symptoms, the most reported were pain, fatigue, insomnia, and loss of appetite. At the opposite extreme were dyspnea, nausea and vomiting, with a mean score of 81.9 and 86.1, respectively. The item relating to Financial Difficulty represented a factor that negatively influences the Quality of Life with representation of 44.4 on the average score. Thus, we conclude that the interaction between clinical situation and treatments for the coexisting disease have cumulative and deleterious effects on Quality of Life, emphasizing the specific concerns related to cancer. It is worth mentioning that the predictive factors for Health-Related Quality of Life identified in this study should receive more attention in the health care practice, they may represent also starting points for future studies that address in depth the different aspects involving the QOL of cancer patients.